Why Can’t a Woman be More Like a Man?: Frauen (und Männer) in den Nebenkammern der königlichen Grabanlagen in Umm el-Qa’ab - Engel, Eva-Maria (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
The article examines archaeological and epigraphic evidence from the subsidiary chambers of the Early Dynastic royal cemetery at Umm el-Qa’ab/Abydos. Not surprisingly it turns out that this group of people was more diverse than the often used modern descriptions as “artisans and concubines” reveal.